Merging internal divisions into one entity : leadership communication in change management - Lienen, Vanessa zur (2021)
The purpose of this thesis is to elaborate the impact of leaders’ (un-)transparent communication on employees’ perception of organizational change in regard to their occupational identities. To do so, a case study was conducted in a German company that underwent organizational change concerning two departments that were decided to be merged into one with a new, mutual team leader in order to improve organizational performance and efficiency. The main method of data collection was interviewing employees of the affected departments, as well as the new team leader. To analyze the interview-data, Interpretative Phenomenological Analysis (IPA) was used to illustrate the individual groups’ lived experience of change and especially of the announcement of change and based on their collective work identities. As a specific focus, I am elaborating the groups’ perceptions of “the others” and their intergroup relationships. As a result, this study demonstrates not only the impact of communication on employees’ perception prior to change, but also how perceptions develop and can be modified with adjusting leadership and communication style. The findings of this case study imply that untransparent top-down communication leads to fear, uncertainty and resistance regarding change, that could be avoided through more transparent and responsive communication from the management. In this particular case, the actual change has been perceived as less impactful and crucial than previously imagined by the employees. An important factor, however, was not only the factual execution of change that was perceived as less apparent than expected, but also the altered and revised communication style that the new team management implemented towards her subordinates.